Chemotherapy for the treatment of intracranial glioma in dogs - José-López, Roberto (Frontiers in Veterinary Science, 2023)
Gliomas are the second most common primary brain tumor in dogs and although they are associated with a poor prognosis, limited data are available relating to the efficacy of standard therapeutic options such as surgery, radiation and chemotherapy. Additionally, canine glioma is gaining relevance as a naturally occurring animal model that recapitulates human disease with fidelity. There is an intense comparative research drive to test new therapeutic approaches in dogs and assess if results translate efficiently into human clinical trials to improve the poor outcomes associated with the current standard-of-care. However, the paucity of data and controversy around most appropriate treatment for intracranial gliomas in dogs make comparisons among modalities troublesome. To further inform therapeutic decision-making, client discussion, and future studies evaluating treatment responses, the outcomes of 127 dogs with intracranial glioma, either presumed (n = 49) or histologically confirmed (n = 78), that received chemotherapy as leading or adjuvant treatment are reviewed here. This review highlights the status of current chemotherapeutic approaches to intracranial gliomas in dogs, most notably temozolomide and lomustine; areas of novel treatment currently in development, and difficulties to consensuate and compare different study observations. Finally, suggestions are made to facilitate evidence-based research in the field of canine glioma therapeutics.